UNVEILING THE CYTOTOXIC POTENTIAL OF HYLOCEREUS COSTARICENSIS (F.A.C. WEBER) BRITTON AND ROSE LEAF: PHYTOCHEMICAL PROFILING AND MOLECULAR DOCKING INSIGHTS - ASHPAK TAMBOLI; DEVATA SHINDE; NAZIYA TAMBOLI; KIRAN PATIL; JYOTIRAM SAWALE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Hylocereus costaricensis (F.A.C. Weber) Britton and Rose, a member of the Cactaceae family, is a well-known plant for its anticancer properties. This study evaluates the gas chromatography-mass spectrometry (GC-MS) analysis, molecular docking and in vitro anticancer activity of ethanolic (ETH) and aqueous (Aq.) extracts derived from its leaves. Methods: GC-MS analysis was utilized to screen plant extracts and identify pharmacologically active compounds. The physicochemical and pharmacokinetic properties of n-hexadecanoic acid, octadecanoic acid, and 17-pentatriacontene were analyzed using SwissADME. Molecular docking studies were also conducted using AutoDock software to evaluate the binding interactions of these three phytoconstituents with the glucose regulatory protein 78 (GRP78) receptor. In addition, the brine shrimp lethality bioassay was performed to assess the in vitro cytotoxic activity of the ETH and Aq. extracts. Results: GC-MS analysis of the ETH extract identified 19 bioactive compounds. Molecular docking showed strong binding of n-hexadecanoic acid, octadecanoic acid, and 17-pentatriacontene to the GRP78 receptor. In vitro cytotoxicity assay revealed dose-dependent effects, with the Aq. extract displayed greater toxicity (LC50: 6.6 μg/mL; mortality: 50±0.94% to 86.66±0.33%) compared to the ETH extract (LC50: 18.57 μg/mL; mortality: 43.33±0.66% to 83.33±0.66%), both showed significant cytotoxicity at higher concentrations (p<0.05, p<0.01). Conclusion: The bioactive compounds present in H. costaricensis may contribute to its pharmacological properties and hold significant potential for the development of novel therapeutic targets. Among the three studied phytoconstituents, n-hexadecanoic acid exhibited the strongest cytotoxic potential, as indicated by its highest binding affinity in molecular docking analysis.